Half-time re-warm up increases performance capacity in male elite soccer players - Edholm, P.; Krustrup, P.; Randers, M. B. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study investigated the acute effects of a half-time re-warm up on performance and movement patterns in soccer match play. Using a crossover design, 22 professional male players performed traditional passive rest (CON) or a low-intensity re-warm up (RW) during the half-time period of two soccer matches. Before and after the first half and before the second half, maximal sprint and jump performance were evaluated. Time-motion analysis of the first 15 min of each half was conducted. Sprint and jump performance were reduced (P < 0.05) by 2.6% and 7.6%, respectively, during the half-time period in CON, whereas sprint performance was maintained and the decrement in jump performance (3.1%; P?<?0.05) was lower after RW. No significant interaction for high-intensity running was observed, but less defensive high-intensity running was observed after RW than CON (0.14 ± 0.06 vs 0.22 ± 0.07?km; P < 0.01). Moreover, RW had more possession of the ball in the beginning of the second half. In conclusion, traditional passive half-time rest leads to impaired sprint and jump performance during the initial phase of the second half in professional soccer players whereas a re-warm up effectively attenuates such deteriorations. Less defensive high-intensity running and more ball possession were observed after RW, indicating a game advantage at the onset of the second half.